FROM MODERATISM TO FUNDAMENTALISM; Portrait of Shifting the Religious Understanding of Makassar Islamic Students - Syamsurijal Syamsurijal (JICSA : Journal of Islamic Civilization in Southeast Asian, 2018)
Students have been asked as intellectuals who have high critical power. Therefore students are not only a driver of a social change, but at the same time are not easily influenced or participate in certain currents of thought and understanding, especially if it is related to religious understanding. Students' critical attitude becomes a kind of filter to sort and filter out various religious ideas and ideas. But the view that sees students, especially Muslim students as a critical group, seems to be faltering lately. Instead of being a critical community group with a variety of new religious understandings, Muslim students actually became the target of the new Islamic doctrine of religious understanding. The doctrine of religious understanding is precisely textualism and fundamentals. This qualitative research shows that several large campuses in Makassar were exposed to the Islamic understanding and changed them from moderate Muslim students to Muslim fundamentalist students.